STATENS MUSEUM FOR KUNST: Et museum for kunsthistorien og samtidskunsten - Petersen, Vibeke (Tidsskriftet Antropologi, 2001)
Statens Museum for Kunst is now one of the few art museums in Europe where collections of art from the 14th century to the present day are kept together. However, the need for an expansion of the exhibition area became increasingly urgent, and a wing was added to the museum in 1996. The article’s title indicates, therefore, the framework for the wide field of art covered by the museum. It is relevant to take a closer look at the historical basis for this combination within visual art. Two important players come to mind: Diderot, French art critic and philosopher of the Enlightenment, and in Denmark the art historian Julius Lange. Diderot advanced the idea that contemporary art should be part of the “modern” public museum. If any one person deserves the credited for legitimizing contemporary art as an important category in itself, it is Denis Diderot, for he made the claim the con-temporary art be taken as seriously as was the art of the past. Lange played a leading part in Danish artistic life. His aim to make explicit the criteria for obtaining optimum presentation of the art collections at Statens Museum for Kunst resulted in heated discussions. They have had a decisive influence in Denmark on the ongoing discussions of the importance of contemporary art seen in relation to museums and art history, and on the presentation of art collections and, not least, on what they should represent. In the end of the 20th century the concept of representation has had a dramatic revival. For an insightful con-tribution to this movement, the article points to the American art historian Donald Preziosi’s discussion of the relation between the “modern” public museum and the con-cept of representation.